Transformasi Nilai Agama Sebagai Inovasi Layanan Bimbingan Konseling Islam Berbasis Media Digital (Analisis Konten Pada Akun Instagram @relasi_consulting & @healyourself.Id) - Fauziah, Nabila; Agustina, Agustina; Nurhikmah, Nurhikmah (Jurusan Bimbingan dan Konseling Islam, 2025)
Instagram has become one of the digital media platforms used to deliver Islamic counseling services. In addition to analyzing service innovations, this study also examines the transformation of religious values presented through Islamic counseling Instagram accounts. This research employs a descriptive content analysis approach using Klaus Krippendorff’s content analysis theory, focusing on two Instagram accounts: @relasi_consulting and @healyourself.id. Both accounts claim to provide counseling services and psychological content grounded in Islamic principles. The findings reveal a transformation of religious values as a form of innovation in Islamic counseling services through digital media. This transformation is reflected in three key dimensions: the digitalization of religion, Islamic cybercounseling, and the construction of the digital identity of Muslim counseling practitioners. The study highlights how social media platforms, particularly Instagram, can serve as effective spaces for integrating religious values and counseling practices in the digital era.